PIDAZTA: Structurally Constrained Chelators for the Efficient Formation of Stable Gallium‐68 Complexes at Physiological pH. Issue 45 (11th July 2019) - Farkas, Edit; Vágner, Adrienn; Negri, Roberto; Lattuada, Luciano; Tóth, Imre; Colombo, Valentina; Esteban‐Gómez, David; Platas‐Iglesias, Carlos; Notni, Johannes; Baranyai, Zsolt; Giovenzana, Giovanni B.
Abstract: Two structurally constrained chelators based on a fused bicyclic scaffold, 4‐amino‐4‐methylperhydro‐pyrido[1, 2‐ a ][1, 4]diazepin‐ N, N ′, N ′‐triacetic acids [(4 R*, 10a S* )‐PIDAZTA (L1 ) and (4 R*, 10a R* )‐PIDAZTA (L2 )], were designed for the preparation of Ga III ‐based radiopharmaceuticals. The stereochemistry of the ligand scaffold has a deep impact on the properties of the complexes, with unexpected [Ga(L2 )OH] species being superior in terms of both thermodynamic stability and inertness. This peculiar behavior was rationalized on the basis of molecular modeling and appears to be related to a better fit in size of Ga III into the cavity of L2 . Fast and efficient formation of the Ga III chelates at room temperature was observed at pH values between 7 and 8, which enables 68 Ga radiolabeling under truly physiological conditions (pH 7.4). Abstract : Getting into stride : Bicyclic ligands, namely 4‐amino‐4‐methylperhydro‐pyrido[1, 2‐ a ][1, 4]diazepin‐ N, N ′, N ′‐triacetic acids (PIDAZTAs), have been synthesized as building blocks for the development of 68 Ga‐based radiopharmaceuticals (see graphic). Quantitative radiolabeling was achieved under mild conditions in minutes. The chelators show stereochemistry‐driven thermodynamic and kinetic stability